PERBANDINGAN BESARAN SFERIKAL EKUIVALEN BERDASARKAN METODE PENGUKURAN VISUS SUBJEKTIF DAN OBJEKTIF PENDERITA AMETROPIA PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI - Palangi, Rezky; Lintong, Fransisca; Moningka Moningka, Maya (Universitas Sam Ratulangi, 2014)
Abstract: Ametropia or refractive error of the eye is the case almost every time we encounter in our environment and increasing steadily each year. One of the factors why refractive error often are not fully corrected due to the difference in the value of spherical and cylindrical or spherical equivalent between the examination of subjective and objective visual acuity. This study aims to determine the difference of the results of subjective and objective visual acuity at patiens ametropia. Analytical research methods with cross sectional design. The subjects were taken from a population that is 40 people. Selected subjects who met the inclusion criteria ; suffering that can be in a correction of ametropia with refractive lenses, suffer ametropia in one eye or both and are willing to be examined. The results obtained are very significant differences in spherical equivalent subjective and objective examination of patients with abnormalities of refraction of-0.8D on the right and left eye of the subject. With more negative value of objective examination. By doing so required a certain effort of medical personnel to maximize the refractive examinations on patients in order to minimize the error correction of ametropia. Conclusion: There is differences in spherical equivalent subjective and objective examination. Keywords: spherical equivalent, subjective vision, objective vision Abstrak: Ametropia atau kelainan refraksi mata merupakan kasus yang hampir setiap saat kita jumpai di lingkungan sekitar kita dan meningkat terus setiap tahunnya. Salah satu faktor mengapa kelainan refraksi sering dikoreksi secara tidak penuh akibat perbedaan nilai sferis dan silinder ataupun sferikal ekuivalen antara hasil pemeriksaan visus subjektif dan objektif. Penelitian ini bertujuan untuk mengetahui perbedaan dari hasil pemeriksaan visus subjektif dan objektif pada penderita ametropia. Metode penelitian analitik dengan desain potong lintang. Subyek diambil dari populasi yang ada sejumlah 40 orang. Subyek dipilih yang memenuhi kriteria inklusi, yaitu; menderita ametropia yang dapat di koreksi dengan lensa bias, menderita ametropia pada salah satu mata atau keduanya dan bersedia untuk diperiksa. Hasil yang didapatkan perbedaan sferikal ekuivalen sangat bermakna pada pemeriksaan subjektif dan objektif penderita kelainan refraksi sebesar -0.8D pada mata kanan dan kiri subyek. Dengan nilai pemeriksaan objektif lebih negatif. Dengan begitu diperlukan upaya tertentu dari tenaga medis untuk memaksimalkan pemeriksaan kelainan refraksi pada penderita ametropia agar meminimalkan kesalahan koreksi. Simpulan: terdapat perbandingan besaran sferikal ekuivalen antara pemeriksaan visus subjektif dan objektif. Kata kunci: Sferikal Ekuivalen, visus subjektif, visus objektif